Comparison between Henley jejunal interposition and Roux-en-Y anastomosis as concerns enterogastric biliary reflux levels. - Sousa, J E (1988)
The amount of enterogastric biliary reflux was assessed in patients who previously underwent Henley operation (n = 8) or Roux-en-Y biliary diversion (n = 7) using the radiopharmaceutical 99mTechnetium-DISIDA. Two other groups were investigated: a control group consisting of patients with unoperated duodenal ulcer (n = 10) and a group of patients who underwent Billroth II gastrectomy (n = 7). The length of the interposed segment of jejunum ranged from 20 to 30 cm (median of 22.5 cm) in the Henley patients, and from 30 to 60 cm (median of 40 cm) in the Roux-en-Y group. In Henley patients, the percentage of administered 99mTechnetium-DISIDA that was recovered from the stomach (median of 0.92%) was lower (p less than 0.01) than that obtained for Billroth II patients (median of 32.28%) and did not differ (p greater than 0.10) from that of the Roux-en-Y (median of 0.36%) and duodenal ulcer groups (median of 2.53%). These results indicate that Henley operation is as effective as Roux-en-Y diversion in promoting the reduction of the amount of enterogastric biliary reflux that follows Billroth II distal gastrectomy.